2021
DOI: 10.1016/j.nicl.2021.102609
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of theta-related pro-active control and response inhibition processes in AD(H)D

Abstract: Highlight Theta-related pro-active control is examined in ADHD/ADD. inter-relation of pro-active control and inhibition-relation activity is modulated in AD(H)D. Dynamics between pre-trial and within-trials differs between AD(H)D subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…We focus on theta (4-7 Hz) band, which has been shown to index executive control and response suppression. 22,29,30 Theta synchronization also improves over frontal areas after working memory training 31 and over fronto-parietal areas after mindfulness meditation. 32 Moreover, both Gist reasoning training and learning training have been shown in increase theta synchronization in GoNoGo tasks among older adults with cognitive impairment, suggesting that theta oscillations might index training effects.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We focus on theta (4-7 Hz) band, which has been shown to index executive control and response suppression. 22,29,30 Theta synchronization also improves over frontal areas after working memory training 31 and over fronto-parietal areas after mindfulness meditation. 32 Moreover, both Gist reasoning training and learning training have been shown in increase theta synchronization in GoNoGo tasks among older adults with cognitive impairment, suggesting that theta oscillations might index training effects.…”
Section: Introductionmentioning
confidence: 92%
“…to test the hypothesis that training‐related changes in older adults’ ERPs are related to alteration in oscillatory power and functional connectivity. We focus on theta (4–7 Hz) band, which has been shown to index executive control and response suppression 22,29,30 . Theta synchronization also improves over frontal areas after working memory training 31 and over fronto‐parietal areas after mindfulness meditation 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, individuals build expectancies about upcoming events and the likelihood to engage, e.g., in inhibitory control. This establishes a proactive control state in between the inhibitory requirements/trials, which also reflects different task demands 29,38 . Intriguingly, such proactive control states are related to theta band activity 39 and, even more importantly, are predictive for the neurophysiological processes that occur while (subsequently) engaging in inhibitory control 29,38 .…”
Section: Alcohol-induced Deficits In Reactive Control Of Response Sel...mentioning
confidence: 98%
“…This establishes a proactive control state in between the inhibitory requirements/trials, which also reflects different task demands 29,38 . Intriguingly, such proactive control states are related to theta band activity 39 and, even more importantly, are predictive for the neurophysiological processes that occur while (subsequently) engaging in inhibitory control 29,38 . This shows that understanding how acute alcohol intoxication affects proactive control preceding the actual response inhibition is probably as important as understanding the directly inhibition-associated processes.…”
Section: Alcohol-induced Deficits In Reactive Control Of Response Sel...mentioning
confidence: 98%
“…In EEG research, for example, compared to the inattentive subtype, those with the combined subtype show higher amplitude beta oscillations at electrodes over the sensorimotor cortex during a cued-flanker inhibitory task (thought to reflect weaker motor response planning (12)). They also show weaker source-localized oscillatory theta power over right frontal areas during the pre-trial intervals of a Go/No-Go task (15). However, contradictory evidence complicates this hypothesis: differences in cognitive measures of inhibitory control often fail to distinguish between subtypes, and electrophysiological research has found no differences between inattentive and hyperactive/impulsive subtypes in the event-related potentials thought to underly motor response inhibition (6,16,17,18,19).…”
Section: Introductionmentioning
confidence: 99%